Odpowiedzi

2009-11-22T13:14:45+01:00
2009-11-22T13:28:07+01:00
A. /*6
3(x+3) - 2(x+1)=6* ³/₂
3x+9 - 2x - 2 = 9
3x - 2x= 9 - 9 + 2
x = 2

b. x√2 - 3 = x - 1
√x * √2 - 3 = x - 1
√2x - 3 = x - 1
2x - x = -1 + 3
x = 2

d. (x - 3)(x + 4) - 2(3x - 2) = (x-4)²
x² = 4x - 3x - 12 - 6x + 4 = x² - 8x + 16
x² + 4x - 3x - 6x - x² + 8 x = 16 - 4 + 12
3x = 24 /:3
x = 8

e. 5(x-1)² - 2(x + 3)² = 3(x + 2)² - 7(6x - 1)
5(x² - 2x +1) - 2(x² + 6x + 9) = 3(x² + 4x + 4) - 7(6x - 1)
5x² - 10x + 5 - 2x² - 12x - 18 = 3x² + 12x + 12 - 42x + 7
5x² - 10x - 2x² - 12x - 3x² - 12x + 42x = 12+7 + 18 - 5
8x = 32 /:8
x = 4